IAAF Medical manual (IAAF, 2012)
Umfangreiches, umfassendes Handbuch des internationalen Leichtathlettikverbands zu allen medizinischen Fragen in Zusammenhang mit der Sportart Leichtatheltik und übergreifend. Inhalt: President`s Message Foreword Preface 1. THE FEDERATION MEDICAL ORGANISATION C. Harmon Brown and Bob Adams 1. National Sports Medicine Structures 2. The Federation Medical Officer 3. Planning International Travel 2. SPORTS AND MEDICINE C. Harmon Brown and Birgir Gudjónsson 1. Principles and Ethical Guidelines 2. The Sports Medicine Team 3. Pre-participation Examination 4. Sports Rules and Athlete Safety 3. TRAINING C. Harmon Brown 1. Principles of Training 2. Restoration, Recovery, and Overtraining 4. GROWTH AND DEVELOPMENT C. Harmon Brown 1. Specific Considerations for the Child and Adolescent Athlete 5. SPORTS PSYCHOLOGY Betty Wenz and Keith Henschen 1. Sports Psychology 2. Athlete`s Competition Day Preparation 6. NUTRITION Louise Burke and C. Harmon Brown 1. Nutrition and Athlete Health 2. A Rational Approach to Supplements 7. INJURY PREVENTION Karen Middleton Griffin and Jack Ransone 1. Principles of Injury Prevention 8. EMERGENCY CARE Jack Ransone and Károly Pikó 1. Triage and Action Plans 2. First Aid Management of Acute Sports Injuries 9. SOFT TISSUE DAMAGE AND HEALING Jack Ransone, Gary Geissler, Paul Wilson, and Bob Adams 1. Soft Tissue Damage and Healing: Theory and Techniques 2. Principles of Rehabilitation of the Injured Athlete 3. Therapeutic Modalities 10. SPECIFIC INJURIES BY ANATOMIC SITE Bob Adams and Frédéric Depiesse 1. Ankle and Foot Injuries 2. Lower Extremity Injuries 3. Knee Injuries 4. Spinal Injuries 5. Upper Extremity Injuries 11. ENVIRONMENTAL FACTORS AFFECTING HUMAN PERFORMANCE Fumihiro Yamasawa and C. Harmon Brown 1. Heat and Cold 2. Altitude 3. Air Pollution 4. Jet Lag 12. INFECTIOUS DISEASES Birgir Gudjónsson 1. Infections Associated with Sports 2. Infections at Large 13. SPECIAL ISSUES OF WOMEN ATHLETES C. Harmon Brown and M. Jegathesan 1. Endocrine/Menstrual Factors 2. Gender Verification and Sex Reassignment Policy 14. SPECIAL MEDICAL PROBLEMS C. Harmon Brown and Giuseppe Fischetto 1. Cardiovascular Evaluation 2. Asthma and Exercise-Induced Bronchospasm (EIB) 3. Headaches and Exercise-Induced Anaphylaxis 15. DRUGS IN SPORTS/DOPING CONTROL Birgir Gudjónsson 1. Drugs in Sports 2. Doping Control 16. APPENDICES C. Harmon Brown, Louise Burke, Frédéric Depiesse, Birgir Gudjónsson, M. Jegathasan, Jack Ransone, Fumihiro Yamasawa 1. Olympic Movement Medical Code 2. Planning International Travel 3. Preparticipation Physical Evaluation 4. American College of Sports Medicine Position Statement on Heat and Cold Illnesses During Distance Running 5. IAAF Policy on Fluid Replacement 6. On-Site Medical Supplies for Injury Prevention and First Aid 7. Cardiopulmonary Resuscitation (CPR)/Adult Basic Life Support 8. Differential Diagnosis and Treatment of Exertional Heat Stroke and Heat Exhaustion on Site 9. Differential Diagnosis and Treatment of Exertional Heat Stroke, Heat Exhaustion, and Hyponatremia in a Clinic Setting 10. Recommendations for Minimising Jet Lag 11. General Health and Hygiene: Recommendations for Athletes 12. Respiratory Tract Infections 13. Process for the Management of Gender-Related Issues